2009
DOI: 10.1002/lapl.200910055
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated-emission spectroscopy of fine-grained “garnet” ceramics Nd3+:Y3Al5O12in a wide temperature range between 77 and 650 K

Abstract: Stimulated-emission spectroscopy methods were applied to investigate the temperature behaviour of main laser properties of the ``garnet'' ceramics Nd3+:Y3Al5O12. Obtained results clearly show that this novel form of the garnet gain material is an excellent alternative to the Nd3+:Y3Al5O12 single crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The emission 4 F 3/2 → 4 I 11/2 spectrum at room temperature (figure 2) is dominated by the 1061.4 nm line, usually attributed to the R 2 → Y 3 transition. However, similar to Nd:YAG [25], the almost resonant transition R 1 → Y 2 could participate in this emission, the relative contributions being influenced by their emission cross-sections and by the opposite variation with temperature of the fractions f (R 1 ) and f (R 2 ).…”
Section: Spectroscopic Bases For Selection Of Pump Wavelength and Nd ...mentioning
confidence: 99%
“…The emission 4 F 3/2 → 4 I 11/2 spectrum at room temperature (figure 2) is dominated by the 1061.4 nm line, usually attributed to the R 2 → Y 3 transition. However, similar to Nd:YAG [25], the almost resonant transition R 1 → Y 2 could participate in this emission, the relative contributions being influenced by their emission cross-sections and by the opposite variation with temperature of the fractions f (R 1 ) and f (R 2 ).…”
Section: Spectroscopic Bases For Selection Of Pump Wavelength and Nd ...mentioning
confidence: 99%
“…It was also found that the relative intensity of the two wavelengths of 1061 and 1064 nm depends on the operation temperature and the pump power intensity. Actually, the balance between the rates of spontaneous emissions at 1061 and 1064 nm has earlier been observed in Nd:YAG crystals and ceramics at cryogenic temperatures [19]. Nevertheless, the performance of dual-wavelength Nd:YAG lasers at 1061 and 1064 nm has so far not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage consists in the elimination of the thermal population at the lower laser level to reduce the reabsorption losses [6]. Moreover, cooling the laser crystal to cryogenic temperature can improve the thermal and thermo-optical properties to maintain the beam quality at high-power operation [10][11][12][13][14]. In past few years, the cryogenic Nd:YAG laser at 946 nm has been experimentally studied by several groups [7][8][9].…”
Section: Introductionmentioning
confidence: 99%